Experimental and modeling study of pyrolysis of coal, biomass and blended coal–biomass particles. (1st January 2015) - Wan, Kaidi; Wang, Zhihua; He, Yong; Xia, Jun; Zhou, Zhijun; Zhou, Junhu; Cen, Kefa
Highlights: Pyrolysis of coal, straw, and blended coal–straw particles were studied by using a single-particle reactor system. Experimental data indicated a lack of synergistic effects. A model was developed based on the CPD model to simulate the pyrolysis process of coal and biomass particles. An extended CPD model was proposed to describe the co-pyrolysis characteristics of coal–biomass blends. Abstract: This paper reports a combined experimental and numerical investigation of the pyrolysis characteristics of coal, biomass, and coal–biomass blends. Coal and straw were grounded and pressed into spherical particles with diameter of 8 mm, and blended coal–straw particles were prepared through mixing pulverized coal and straw before pressed into particles. Sample particles were suspended in the center of a single-particle reactor system and devolatilized under different temperatures. The analysis of the time history of the residual mass of particles of coal, straw, and coal–straw blends suggested an absence of synergistic effect between the coal and the straw. In addition, a one-dimensional, time-dependent particle model; based on the chemical percolation devolatilization (CPD) and bio-CPD models; was developed to simulate the pyrolysis of coal and straw particles. The model predictions agree will with the measured data. An extended CPD model was proposed to explain the co-pyrolysis characteristics of coal–biomass blends. Encouraging agreement was found between the predicted and the experimental results of pyrolysis of coal–straw blends.